'Ahead of all Beaten Tracks': Ryle, Heidegger and the Ways of Thinking. Issue 1 (1st November 2012) - Williams, Emma
<x xml:space="preserve">Abstract</x> The purpose of this article is to examine two philosophical accounts of thinking—yet examine them anew by considering what I take to be their under‐examined relationship. These are the accounts of Gilbert Ryle and Martin Heidegger. It is often supposed that these two philosophers belong to differing, even conflicting, philosophical traditions. However, this article will seek to demonstrate that an unrecognised affinity exists between them on account of their shared endeavour to venture ahead of the 'beaten tracks' of Modern Philosophy. In this way, I will seek to challenge a number of preconceptions that inform the way these thinkers are interpreted and utilised by philosophers of education—particularly preconceptions about Ryle that appear to be active in much 'thinking skills' literature. Through exploring certain under‐attended‐to aspects of Ryle's work (including his early essays on phenomenology and his later reflections on the nature of thinking) this article will seek to offer a renewed investigation into these two philosophical accounts of thinking, in terms of both their limitations and the ways of thinking they open.